ANALISIS KADAR ASAM LINOLEAT DAN ASAM LINOLENAT PADA TAHU DAN TEMPE YANG DIJUAL DI PASAR TELAGA SECARA GC-MS - Kilo, Ahmad Kadir; Isa, Ishak; Musa, Weny JA (Sainstek, 2012)
The purpose of this research is to measure Linoleic Acid and Linolenic Acid Level in Tofu and Fermented Soybean Cake through Gas Chromatography-Mass Spectrometry. This is a laboratory research that use tofu and fermented soybean cake from Telaga traditional market as the sample of research. Sample was extracted by using n-hexane to produce oil. Then, oil was hydrolyzed by using KOH liquid and H2SO4 as a catalyst to get the free fatty acid. Then, it was converted to metil ester by using CH3OH as a solvent and H2SO4 as a catalyst for the necessity of fatty acid analysis. This research used Gas Chromatography-Mass Spectrometry to identify Linoleic Acid and Linolenic Acid Level in the sample. The analysis result shows that the biggest component of metil ester in tofu and soybean cake are dominated by metil linoleic (metil 9.12-octadekadienoat) with percentage 55.25% and 27.08% for each. Mean, the linolenic acid in tofu and fermented soybean cake cannot be detected by GC-MS. It is caused by the fermentation time, high temperature during production and fermentation, and humidity in the sample. Therefore, a further research is necessary to investigate level of linolenic acid. In tofu and fermented soybean cake.